Fitoplâncton como alimento para microcrustáceos e rotíferos nos períodos de seca e enchente no lago Tupé, Manaus-AM - Mendes, Raize Castro (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
The lake Tupé, which is located near Manaus, in the Amazonas state, is a black-water lake of great richness of phytoplanktonic and zooplanktonic species. The zooplanktonic organisms may belong to different size categories: microplankton, mesoplankton, and macroplankton; but the phytoplanktonic organisms may belong to picoplankton, nanoplankton, and microplankton. Because of the size difference, the zooplanktonic organisms might be feeding on phytoplanktonic organisms of different sizes. The goal of this research was to evaluate the importance of phytoplankton different fractions as food for microcrustaceans and planktonic rotifers in the low waters period (2015) and rising waters (2016) at the lake Tupé, Manaus-AM. The samples were conducted in two months at the low Waters period and two months in the rising Waters period at the lake Tupé (Reserve of Sustainable Development of Tupé). As sampling criteria, the estimated photic zone extension was used with the assistance of transparency measures by the Secchi disc. A PVC tube of 50 mm in diameter and 3 m in length with a water retention valve which was inserted in this extension and its content was placed in a bucket, homogenized and 2 L samples were taken. At the laboratory, the samples were fractionated in order to obtain the picoplankton, nanoplankton, and microplankton and later the biomass of each fraction was measured through the Chlorophyl-a. An experiment was placed at lake Tupé during 24 hours in the low Waters period and rising water period. The zooplanktonic and phytoplanktonic samples were collected with a PVC tube of 4 m in length, later they were taken to the laboratory to be analyzed. The zooplanktonic organisms. The zooplanktonic organisms were counted and measured. The phytoplankton samples were fractionated in order to obtain the differences in size fraction, and later, the biomass of each fraction was measured. The total low Waters period biomass was 27,03 μg/L, and the total rising Waters biomass was 36,59 μg ̸ L. There were no statistically significant differences between the biomass of the picoplankton, nanoplankton and microplankton in the two periods. The zooplanktonic organisms did not exercised selective predation pressure on just one of the phytoplankton size fractions. Instead, they exercised predation pressure on phytoplankton three size fractions.
Keywords: Picoplâncton; Biomassa